Measuring media‐related health and mental health information acquisition among Latino adults in the United States - DuPont‐Reyes, Melissa J.; Villatoro, Alice; Gama, Giovanni; Tang, Lu (International journal of methods in psychiatric research, 2023)
Objectives We developed and evaluated new media‐related health information acquisition measures for U.S.‐based Latino populations. Methods In 2021, a sample of U.S.‐based Latino adults (N = 1574) self‐completed a 20‐min survey of health information acquisition measures across three language/cultural dimensions: Spanish media, Latino‐tailored media in English, and general media in English. Socio‐demographics were also ascertained. Means and standard deviations for the health acquisition measures were adjusted for age and sex and reported across nativity status. Results The sample was diverse across age, gender, race, ethnicity, socioeconomic status, migration, and language competency. Internal consistency reliability of developed scales was excellent overall and within age, gender, race, ethnicity, and socioeconomic subgroups (Cronbach's alphas = 0.86–0.94). English media scales had higher means overall indicating higher prolonged quantity (i.e., dosage) than Spanish media scales. In contrast, standard deviations for Spanish media scales were higher overall indicating broader reach at lower doses than English media scales. Conclusions Findings suggest English‐language media is popular among Latino populations overall. However, Spanish‐language media retains broad reach through both passive and active exposure. Our findings demonstrate the value of including more nuanced measurement of health information acquisition such as the scales developed in this study to improve health promotion among Latino populations.